Mechanisms for fast cell migration in complex environments. (October 2017) - Vargas, Pablo; Barbier, Lucie; Sáez, Pablo José; Piel, Matthieu
Highlights: Leukocytes have developed specific mechanisms to move in tissues. Specific cytoskeleton arrangements control cell migration in complex environments. Fast leukocytes' migration in complex geometries requires cell plasticity. Interpretation of chemical and physical cues orchestrate cell motility in tissues. Abstract : Cell migration depends on a combination of the cell's intrinsic capacity to move and the proper interpretation of external cues. This multistep process enables leukocytes to travel long distances in organs in just a few hours. This fast migration is partly due to the leukocytes' high level of plasticity, which helps them to adapt to a changing environment. Here, we review recent progress in understanding the mechanisms used by leukocytes to move rapidly and efficiently in intricate anatomical landscapes. We shall focus on specific cytoskeletal rearrangements used by neutrophils and dendritic cells to migrate within confined environments. Lastly, we will describe the properties that facilitate the rapid migration of leukocyte in complex tissue geometries.